KOMUNIKASI PERSUASIF BANK BJB CABANG PEKANBARU DALAM MENUMBUHKAN MINAT MENABUNG DI SIMPANAN PELAJAR (SIMPEL) - Keke Nabila Farahdiba; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Student savings (SimPel) are savings intended for schoolchildren from Paud level to Junior High School level and bank bjb Pekanbaru branch focuses this program at the junior high school level (SMP) focusing on SMPN13 Pekanbaru. This program is implemented in collaboration with SMPN13. Bank bjb Pekanbaru branch chose SMPN13 because SMPN13 is a favorite school in Pekanbaru. Bank bjb Pekanbaru branch is a bank from the Java region that can stand even growing rapidly in the city of Pekabaru . Proven from the data obtained that in 2016 bank bjb Pekanbaru Branch recorded has increased the profit by 60% compared to achievements made in 2015. By Therefore, the writer decided to choose bank bjb as the object of research, because although bank bjb is a bank from Java area but this bank can grow rapidly and even have the above profit from this bank area that is Bank Riau and also have many achievement.This research uses qualitative method with descriptive approach, with research location at SMPN13 Pekanbaru and bank bjb Pekanbaru branch. Subject of research consist of 9 informant chosen by purposive and accidental technique. Data collection is done through observation, interview and documentation. To determine the falidity test of the author data using the method of extension of participation and trinagulasi.The results of this study indicate the credibility of the bank bjb Pekanbaru branch as a communicator, they have expertise (expertness) and trustworthiness (trust wortness). Dalan convey the message bank bjb Pekanbaru branch deliver verbal messages that include clarity, kelugasan and accuracy and nonverbal messages in the form of use of devices in the form of savings books and ATM SimPel. Bank bjb Pekanbaru uses personal channels in the form of direct, non-personal communication in the form of cooperation with the mass media. Pesuasif communication effect from bank bjb Pekanbaru branch to students of SMPN 13 Pekanbaru is an increase and understanding of saving on student self and action follow program of SimPel by bank bjb branch Pekanbaru.Key words : Bank, bjb, Persuasive